Snappy App: a mobile continuous performance test with physical activity measurement for assessing hyperactivity disorder - Young, Zoe; Craven, Michael P.; Groom, Madeleine J.; Crowe, John A. (Springer Verlag, 2014)
A Continuous Performance Test (CPT) was incorporated into a smartphone application (App) to measure three symptom domains associated with Attention Deficit Hyperactivity Disorder (ADHD); attention, impulsivity and hyperactivity. The App was pilot tested on 11 healthy adults over three testing sessions. No differences in performance were found between testing sessions suggesting good test consistency. A decrement in performance over time was only found for one measure of attention and on one testing session. The CPT showed some sensitivity to ADHD-related symptoms where self-reported impulsive behaviour was related to the CPT measures of impulsivity and activity. User acceptability was good although some design improvements were suggested. Further pilot testing of the App in a clinical population is needed.